Role of a Max Yeast Culture Probiotic in Potentiating the Growth Performance of Commercial Broiler (Progressive Agriculture, 2014)
The present study is under taken to determine the body weight gain of broilers, to determine carcass yield or dressing percentage of broilers, to determine feed conversion ratio of broilers, to enumerate the colonizing micro flora in the gut of broilers. A total of 80 day-old broiler chicks were divided into two main groups I and II with 40 chicks in each. Group I was supplemented with Probiotic (Max Yeast Culture gm/kg feed) containing feed and chicks of group II was supplemented with conventional feed. Group I and II was again subdivided into two subgroups as group A, B and C, D respectively on 6 days of age. Birds of subgroups A and C were vaccinated with ND vaccine (BCRDV) and birds of subgroups C and D were kept as unvaccinated. The result evidenced the following information: (a) The total viable count (TVC) and total coliform count (TCC) were significantly (P